Optimalisasi Fasilitas Listrik Dermaga dan Peningkatan Keandalan Auxiliary Engine Kapal terhadap Efisiensi Biaya Operasional Kapal di Pelabuhan Tanjung Emas - Aditya M. Dewi; Prasongko Prasongko; Muhammad A. L. Pambudi (SAINTARA, 2023)
This research aims to analyze the efficiency of ship operational costs obtained by using dock electricity facilities, which are used as a substitute for using Auxiliary Engines (auxiliary engines), which use fuel oil. The research method used was a mixed method (a combination of qualitative and quantitative). The analysis technique used is cost-benefit analysis (CBA) by comparing fuel oil and shore connections. The analysis results show that using shore connections can reduce ship operational costs by IDR. 6,016,349,488 / year in terms of efficient use of fuel costs, while regarding the reliability of the Auxiliary Engine (AE), the efficiency is up to Rp. 1,903,000,000/ year. After using a shore connection as a substitute for AE, which uses fuel, there will be no damage to the AE, and it can reduce ship repair costs. The use of electricity facilities via shore connection can also support the achievement of the government program, namely Go Green Port (Environmental Friendly), by reducing air pollution from ship exhaust gases as an implementation of MARPOL Annex VI and implementing Permenhub regulation number 29 of 2014 article 37 concerning pollution prevention maritime environment. However, the disadvantages of using shore connections are that the investment costs required for installing cable connections on ships are quite large, and there is an increase in the cost of electricity usage, which is directly proportional to the increase in government electricity rates every year.